2005
DOI: 10.1159/000084105
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Renal Dysfunctions in Family Members of Patients with Balkan Endemic Nephropathy

Abstract: Background/Aim: Recent studies have questioned whether new cases of Balkan endemic nephropathy (BEN) are occurring. The aim of the present study was to find out whether new members with renal dysfunctions can be identified among family members of BEN patients from the Kolubara region. Methods: The study included 47 family members of 5 BEN patients on hemodialysis (HD) and 17 members of 3 non-BEN patients on HD. Their medical and epidemiological histories were taken, an objective survey made, and all persons we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 17 publications
2
19
1
2
Order By: Relevance
“…However, in two endemic municipalities of the outer Belgrade area (i.e., Barajevo and Lazarevac), the number of incident BEN cases did not change over the previous three decades. [5,6] One of its most peculiar characteristics is a strong association with upper urothelial cancer (UUC). [7] BENrelated UUC has the same histological features as other forms of UUC in general, but is more frequently bilateral, less frequently affects the bladder, and has a sex ratio close to 1. Living in an endemic settlement is a prerequisite for BEN diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, in two endemic municipalities of the outer Belgrade area (i.e., Barajevo and Lazarevac), the number of incident BEN cases did not change over the previous three decades. [5,6] One of its most peculiar characteristics is a strong association with upper urothelial cancer (UUC). [7] BENrelated UUC has the same histological features as other forms of UUC in general, but is more frequently bilateral, less frequently affects the bladder, and has a sex ratio close to 1. Living in an endemic settlement is a prerequisite for BEN diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[5] However, it has recently been reported that the prevalence of hypertension in endemic villages was high, although it is the same as in nonendemic rural parts. [21,22] Hypertension was found in 43% of BEN and 35% of non-BEN family members. [21] In the endemic villages, the prevalence of hypertension was the same as in control (51.7% vs 49.2%).…”
Section: Hypertensionmentioning
confidence: 99%
“…[21,22] Hypertension was found in 43% of BEN and 35% of non-BEN family members. [21] In the endemic villages, the prevalence of hypertension was the same as in control (51.7% vs 49.2%). [22] It was suggested that the higher prevalence of hypertension is likely due, in addition to older age, to the fact that that this group contains the greatest number of obese individuals.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,8 Existing literature and prior studies have demonstrated that increased β 2 -microglobulin and reduced kidney length were associated with both BEN patients and their healthy offspring. [9][10][11][12][13][14][15] Moreover, increased C-reactive protein (CRP) and narrow kidney cortex width were related to a parental history of BEN (PHB) before the disease manifestation. A reduced CCr was connected to both BEN patients and offspring, and it was inversely correlated with kidney sizes in BEN patients.…”
Section: Introductionmentioning
confidence: 99%